2015
DOI: 10.1017/s0266467415000292
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure ofManilkara maxima(Sapotaceae), a tree species from the Brazilian Atlantic forest

Abstract: Abstract:Habitat fragmentation may lead to spatial genetic structuring of plant populations, but the magnitude of this effect differs among species. In this study, the effects of fragmentation on spatial genetic structure ofManilkara maxima, an ecologically important tree species endemic to the Atlantic forest of southern Bahia, Brazil, were examined. To address this issue, 222 individuals were sampled across two large-forest sites (200 and 400 ha) and one site comprising eight small fragments (5, 10 and 25 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…Thus, our two working hypotheses were confirmed by this study. First, the decline in FSGS over the life history was previously reported for various tree species ( Hamrick et al, 1993 ; Epperson and Alvarez-Buylla, 1997 ; Lian et al, 2008 ; Schroeder et al, 2014 ; Ganzhorn et al, 2015 ), and has been attributed to the demographic thinning of individuals. Second, the previously mentioned inbreeding depression might also have weakened the FSGS in our study.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, our two working hypotheses were confirmed by this study. First, the decline in FSGS over the life history was previously reported for various tree species ( Hamrick et al, 1993 ; Epperson and Alvarez-Buylla, 1997 ; Lian et al, 2008 ; Schroeder et al, 2014 ; Ganzhorn et al, 2015 ), and has been attributed to the demographic thinning of individuals. Second, the previously mentioned inbreeding depression might also have weakened the FSGS in our study.…”
Section: Discussionmentioning
confidence: 89%
“…maxima , genetic diversity (H O and H E ) in large forests and recently shaped forest fragments (35 y old) also fell within the same range (0.50–0.74; Ganzhorn et al . 2015). Manilkara zapota (and closely related species) therefore seems to maintain high genetic diversity in a variety of habitats, including continuous forest, young and old forest fragments and managed populations (Thompson et al .…”
Section: Discussionmentioning
confidence: 99%
“…maxima ) that did have more replicates (eight fragments and two large forests) (Ganzhorn et al . 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several studies within the Sapotaceae family have reported high levels of genetic diversity in wild species such as: Argania spinosa L. Skeels (H E = 0.67, Yatrib et al 2017); Manilkara maxima (H E = 0.67, Ganzhorn et al 2015); Pouteria reticulata (Engl.) Eyma (H E = 0.71, Schroeder et al 2014); Manilkara zapota (H E = 0.95, González-Hernández et al 2012); and Manilkara huberi (Ducke) Standl (H E = 0.86, Azevedo et al 2007; H E = 0.78, Rennó 2007).…”
Section: Genetic Diversitymentioning
confidence: 99%